Etimology And Biological Control Of Sheath Rot Disease Of Rice - Mini George (Department of Plant Pathology, College of Agriculture, 1995)
Sympotmatology and etiology of sheath rot disease of rice was investigated and attempts were made in the biological control of the disease. The sheath rot disease of rice initiated as brown oblong lesions on the flag leaf sheath were surrounded by light yellow halo initially. On maturity, these lesions turned dark brown with grey centres. Slight brown discolouration was also seen on the second and third leaf sheaths. Panicles were found choked inside the sheath or partially emerged with discoloured grains.